LBPS 02–42 ADDITIONAL TOOL TO IMPROVE ADHERENCE TO LIFESTYLE MODIFICATION AND MEDICATIONS. (September 2016) - Gasimov, Zaur; Humbatova, Leyla
Abstract : Objective: Non-adherence and weak adherence to lifestyle modification and medications remain problem in the most subjects with mediate and high risk for development of cardiovascular diseases. Motivational interview with use of European Heart SCORE risk calculator is a good tool to increase adherence to lifestyle change and medications. Design and Method: We decided to study the impact of common use of SCORE and figures of statistical data demonstrating risk of lung cancer according to duration and intensity of smoking and according to age men stop smoking. Total of 48 men, age from 40 to 60, SCORE > 10, all heavy smokers (10–40 cigarettes per day), 65% with Hypertension (stage I-II-JNC 7), 80%- with high total cholesterol were divided into two groups:1-st group were interviewed with calculation by SCORE tool without demonstration additional figures of statistics of risk of smoking for cancer, 2-nd group were interviewed with presentation of these figures additionally to SCORE risk calculator. Results: After 1 year follow up period, males from the 2-nd group more significantly reduced daily cigarettes consumption compare to the 1-st group, adherence to antihypertensive medications, statins and aspirin was higher in the 2-nd group, but not significantly. Conclusions: Traditional 10 year risk calculator of fatal CVD - HEARTSCORE is an effective tool to improve adherence to lifestyle modification and medications but becoming more effective when use with cancer risk figures.